Seat belt surface coating for preventing seawater erosion and preparation method thereof

By applying a coating composed of polyurethane resin, ammonium salt, nanoclay and sodium oleate on the surface of marine seat belts, the problem of corrosion of seat belts in the marine environment is solved, significantly improving waterproof and corrosion resistance, and extending service life.

CN119752297APending Publication Date: 2025-04-04SHANGHAI CHENGGE SAFETY EQUIP GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411902546.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing marine safety belts are susceptible to brine corrosion in the marine environment, resulting in rust in metal parts, aging and degradation of fiber webbing materials, reducing strength, and threatening the personal safety of users.

Method used

A safety belt surface coating that is anti-seawater erosion is used, including polyurethane resin, fillers, corrosion inhibitors, plasticizers, solvents, and coupling agents. The corrosion inhibitor is composed of ammonium salt, nanoclay and sodium oleate. Through ultrasonic dispersion and adsorption, sodium oleate is firmly adsorbed on the surface of the fiber webbing to form a tough protective film.

Benefits of technology

This coating can significantly improve the waterproof and corrosion resistance of the seat belt, extend the service life, reduce the corrosion current density, and significantly improve the durability of the seat belt in the marine environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203584560000061
    Figure BDA0005203584560000061
  • Figure BDA0005203584560000071
    Figure BDA0005203584560000071
Patent Text Reader

Abstract

The present application relates to the technical field of coatings, and specifically discloses a surface coating for seat belts that resist seawater erosion and a preparation method thereof. A surface coating for seat belts that resist seawater erosion comprises the following components by weight: 26-35 parts of polyurethane resin; 3-8 parts of filler; 8-16 parts of corrosion inhibitor; 3-9 parts of plasticizer; 30-55 parts of solvent; 5-10 parts of coupling agent; the raw materials for preparing the corrosion inhibitor include: ammonium salt, nanoclay and sodium oleate. The surface coating for seat belts that resist seawater erosion of the present application can be used for coating the surface of seat belts, and the combination of ammonium salt, nanoclay and sodium oleate improves the protective effect of the coating, which has the advantages of improving the seawater corrosion resistance of metals and fibers for a long time, good water resistance and strong adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coatings, and more specifically, to a surface coating for a safety belt that is resistant to seawater erosion and a preparation method thereof. Background Art

[0002] Marine safety belts play an important role in ensuring the safety of personnel in the marine environment, preventing the risk of personnel falling from the ship while working. In addition to having good safety performance, marine safety belts should also be able to withstand exposure to salt water and harsh marine environments, and be able to resist corrosion and degradation from salt water.

[0003] Safety belts consist of metal parts and fiber webbing parts. In the marine environment, safety belts are exposed to seawater containing high concentrations of salt, microorganisms, dissolved oxygen and other complex chemical components for a long time. The interaction of these factors causes the material of the safety belt to gradually corrode, such as rust on the metal parts and aging and degradation of the fiber webbing materials, which reduces the strength of the safety belt and threatens the personal safety of the user. At present, the protective effect of the safety belt is improved by coating.

[0004] In order to improve the corrosion resistance of seat belts, sodium oleate is currently added to the coating as a corrosion inhibitor. Sodium oleate can be adsorbed on the surface of metal parts to form a protective film, which prevents corrosive substances such as chloride ions in seawater from contacting the metal. It also acts as a waterproofing agent to improve the waterproof effect of the webbing.

[0005] However, the durability of sodium oleate waterproofing is not good enough. After being immersed in water for a long time, it will gradually fall off the surface of the ribbon, resulting in a decrease in waterproof performance. On the other hand, the amount of sodium oleate used needs to be precisely controlled. Too much sodium oleate may make the surface of the ribbon greasy, affecting the appearance and feel of the ribbon, while too little sodium oleate will not achieve the ideal waterproof effect. Summary of the invention

[0006] In order to reduce the greasiness problem and improve the waterproofness of the webbing, the present application provides a safety belt surface coating that is resistant to seawater erosion and a preparation method thereof.

[0007] In a first aspect, the present application provides a safety belt surface coating that is resistant to seawater erosion, and adopts the following technical solution: a safety belt surface coating that is resistant to seawater erosion, comprising the following components by weight: Polyurethane resin 26-35 parts; 3-8 parts of filler; 8-16 parts of corrosion inhibitor; 3-9 parts of plasticizer; 30-55 parts of solvent; 5-10 parts of coupling agent; The raw materials for preparing the corrosion inhibitor include: ammonium salt, nano clay and sodium oleate.

[0008] By adopting the above technical solution: polyurethane resin as the main film-forming substance can be tightly attached to the surface of the safety belt to form a tough protective film, while making the webbing have good flexibility, wear resistance and chemical corrosion resistance, and resisting the erosion of seawater and mechanical wear. The addition of organic silane coupling agent can increase the adhesion between the coating and the safety belt base material and improve the bonding strength of the coating; on the other hand, it has a hydrophobic effect, reducing the adhesion and penetration of seawater on the coating surface. The corrosion inhibitor mainly inhibits the corrosion of metal parts by seawater, and at the same time plays a waterproof role on the webbing to improve the protective effect of the webbing.

[0009] The original single sodium oleate dosage was replaced with a combination of ammonium salt, nanoclay and sodium oleate, reducing the dosage of sodium oleate to reduce the greasy problem. The introduction of nanoclay is a type of layered material with negatively charged sheets on the surface. The positively charged cations of ammonium salts are adsorbed between the nanoclay layers, and the other end is adsorbed with the negatively charged oleate ions in water, thereby firmly adsorbing sodium oleate on the surface of the fiber ribbon, which is not easy to detach, thereby maintaining a long-term effective waterproof and anti-corrosion effect.

[0010] Optionally, the preparation method of the corrosion inhibitor is: adding ammonium salt and nano clay into water, mixing, then adding sodium oleate, mixing, ultrasonically dispersing, filtering to remove the filtrate, and drying to obtain the corrosion inhibitor.

[0011] Optionally, the weight ratio of the sodium oleate, ammonium salt and nanoclay is 1:0.8-1.2:0.3-0.5.

[0012] By adopting the above technical solution: when the dosage of sodium oleate, ammonium salt and nano clay is within the above range, the prepared coating has the best waterproof effect on the ribbon, thereby improving the seawater resistance of the ribbon.

[0013] Optionally, the amine salt has 12-18 carbon atoms.

[0014] Optionally, the amine salt is one of dodecyl ammonium sulfate, hexadecyl ammonium chloride, and octadecyl quaternary ammonium salt.

[0015] By adopting the above technical solution, the above ammonium salts can all be used as corrosion inhibitor components of the present application, and can effectively improve the anti-seawater corrosion effect of the webbing.

[0016] Optionally, the filler is graphene nanosheets.

[0017] By adopting the above technical solution: graphene has excellent conductivity, mechanical properties and chemical stability. In addition, graphene can also enhance the mechanical strength and wear resistance of the coating.

[0018] Optionally, the plasticizer is dioctyl phthalate.

[0019] By adopting the above technical solution: dioctyl phthalate can improve the flexibility and plasticity of the coating, and prevent the coating from cracking at low temperatures or under stress. It can reduce the glass transition temperature of the coating, improve the cold resistance and impact resistance of the coating, and enable the coating to maintain good performance in a complex marine environment.

[0020] Optionally, the solvent is one of toluene and xylene.

[0021] By adopting the above technical solution: dissolving the various components of the coating so that the various components are fully mixed during the mixing process to obtain a coating system, and as the solvent evaporates during the construction process, the coating is solidified on the surface of the safety belt.

[0022] In a second aspect, the present application provides a method for preparing a surface coating for a safety belt that is resistant to seawater erosion, using the following technical solution: A safety belt surface coating for preventing seawater erosion comprises the following steps: The polyurethane resin, filler, corrosion inhibitor, plasticizer, solvent and coupling agent are mixed to obtain the product.

[0023] By adopting the above technical solution: fewer process steps, simple and efficient, it is conducive to industrial large-scale preparation of coatings, and the prepared coatings can effectively improve the protection of safety belts in marine environments and effectively prevent seawater erosion. The corrosion current density is tested, compared with 0.3μA / cm for safety belts without coating. 2 The coating of the present application reduces the corrosion current density of the seat belt to less than 0.01μA / cm 2 , corrosion resistance and good.

[0024] In summary, this application has the following beneficial effects: A corrosion inhibitor is added to the coating of the present application. The corrosion inhibitor can form a film on the metal surface and prevent corrosive ions such as chloride ions in seawater from contacting the metal, thereby slowing down the corrosion rate. At the same time, the corrosion inhibitor has a waterproof effect on the webbing part, reducing water penetration and erosion, and effectively extending the service life of the seat belt.

[0025] 2. The present application improves the corrosion inhibitor by using a compound combination of sodium oleate, ammonium salt and nanoclay, wherein the cation of the ammonium salt carries a positive charge and is adsorbed between the nanoclay layers, and the other end is adsorbed with the oleate ion which is negatively charged in water, so that the sodium oleate is firmly adsorbed in the nanoclay and retained on the surface of the ribbon, thereby improving the waterproof effect; 3. The method of the present application has a simple process and is conducive to the industrial scale-up of coating preparation. The prepared coating can significantly reduce the corrosion current density of the seat belt and provide long-term and effective waterproof performance. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with the examples. The sources of the components are as follows, except for the following special instructions, the components are commercially available: Nanoclay, kaolin, was collected from Shijiazhuang Fengming Mineral Products Co., Ltd., with a particle size of 6000 mesh, a whiteness of 91.6%, a silicon dioxide content of 51%, and an aluminum oxide content of 45.1%; Polyurethane resin was obtained from Anhui Dawei Huatai New Material Technology Co., Ltd., model AH-K100-1; Graphene nanosheets were obtained from Chengdu Jiacai Technology Co., Ltd., model JCHGNP; Sodium oleate was obtained from Jinan Bio Chemical Co., Ltd.; Dioctyl phthalate was obtained from Shandong Zhongwei New Materials Co., Ltd.

[0027] Preparation Example 1 A corrosion inhibitor is prepared by the following steps: adding 8g of ammonium salt (hexadecyl ammonium chloride) and 3g of nanoclay to 1L of water, stirring and mixing at a speed of 1000rpm for 20min, then adding 10g of sodium oleate, stirring and mixing at a speed of 1500rpm for 20min, ultrasonically dispersing for 30min, filtering to remove the filtrate, and drying at 50°C for 20min to obtain the corrosion inhibitor.

[0028] Preparation Example 2 A corrosion inhibitor is prepared by the following steps: adding 10g of ammonium salt (ammonium dodecyl sulfate) and 4g of nanoclay to 1L of water, stirring and mixing at a speed of 1000rpm for 20min, then adding 10g of sodium oleate, stirring and mixing at a speed of 1500rpm for 20min, ultrasonically dispersing for 30min, filtering to remove the filtrate, and drying at 50°C for 20min to obtain the corrosion inhibitor.

[0029] Preparation Example 3 A corrosion inhibitor is prepared by the following steps: adding 12g of ammonium salt (octadecyltrimethylammonium chloride) and 5g of nanoclay to 1L of water, stirring and mixing at a speed of 1000rpm for 20min, then adding 10g of sodium oleate, stirring and mixing at a speed of 1500rpm for 20min, ultrasonically dispersing for 30min, filtering to remove the filtrate, and drying at 50°C for 20min to obtain the corrosion inhibitor.

[0030] Comparative Preparation Example 1 A corrosion inhibitor, which is different from Preparation Example 2 in that no ammonium salt is added.

[0031] Comparative Preparation Example 2 A corrosion inhibitor, which is different from Preparation Example 2 in that no nano clay is added.

[0032] Comparative Preparation Example 3 A corrosion inhibitor is different from Preparation Example 2 in that the dosage of ammonium salt and nanoclay is different, and the weight ratio of the dosage of ammonium salt, nanoclay and sodium oleate is 0.6:0.24:1.

[0033] Comparative Preparation Example 4 A corrosion inhibitor is different from Preparation Example 2 in that the dosage of ammonium salt and nanoclay is different, and the weight ratio of the dosage of ammonium salt, nanoclay and sodium oleate is 1.5:0.55:1.

[0034] Example 1 A safety belt surface coating for preventing seawater erosion, wherein the components and their corresponding weights are shown in Table 1, and the coating is prepared by the following steps: Add polyurethane resin to the solvent (toluene), stir and mix at 300 rpm for 60 min, then add silane coupling agent KH560, continue stirring for 15 min, and obtain mixed solution A; Filler (graphene nanosheets) and corrosion inhibitor (prepared in Preparation Example 1) were added to mixed solution A, and ultrasonic dispersion was performed at 800 watts for 60 minutes. Then, a plasticizer (dioctyl phthalate) was added, and the mixture was stirred and mixed at 800 rpm for 15 minutes.

[0035] Example 2 A safety belt surface coating for preventing seawater erosion, wherein the components and their corresponding weights are shown in Table 1, and the coating is prepared by the following steps: Add polyurethane resin to the solvent (toluene), stir and mix at 400 rpm for 45 min, then add silane coupling agent KH560, continue stirring for 20 min, and obtain mixed solution A; Filler (graphene nanosheets) and corrosion inhibitor (prepared in Preparation Example 1) were added to mixed solution A, and ultrasonic dispersion was performed at a power of 1000 watts for 45 minutes. Then, a plasticizer (dioctyl phthalate) was added, and the mixture was stirred and mixed at a speed of 800 rpm for 20 minutes.

[0036] Example 3 A safety belt surface coating for preventing seawater erosion, wherein the components and their corresponding weights are shown in Table 1, and the coating is prepared by the following steps: Add polyurethane resin to the solvent (xylene), stir and mix at 500 rpm for 30 min, then add silane coupling agent KH560, continue stirring for 30 min, and obtain mixed solution A; Filler (graphene nanosheets) and corrosion inhibitor (prepared in Preparation Example 1) were added to mixed solution A, and ultrasonic dispersion was performed at a power of 1200 watts for 30 minutes. Then, a plasticizer (dioctyl phthalate) was added, and the mixture was stirred and mixed at a speed of 800 rpm for 30 minutes.

[0037] Comparative Example 1-2 A surface coating for a safety belt that is resistant to seawater erosion, which differs from Example 2 in that the amounts of the components used are different, as specifically shown in Table 1.

[0038] Table 1 Components and their weights in Examples 1-3 and Comparative Examples 1-2 (kg) Components Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Solvents 30 42 55 42 42 Polyurethane resin 25 30 35 30 30 Coupling agent 5 7 10 7 7 filler 3 5 8 5 5 Corrosion Inhibitor 8 12 16 6 20 Plasticizers 3 6 9 6 6 Comparative Example 3 A safety belt surface coating for preventing seawater corrosion, which differs from Example 2 in that an equal amount of sodium oleate is used instead of a corrosion inhibitor.

[0039] Examples 4-5, Comparative Examples 4-7 A safety belt surface coating for preventing seawater corrosion is different from Example 2 in that the usage of the corrosion inhibitor refers to the following Table 2, but the amount of the corrosion inhibitor remains unchanged.

[0040] Table 2 Usage of corrosion inhibitors in Examples 4-5 and Comparative Examples 4-7 Example 4 5 \ \ Preparation Example of Corrosion Inhibitor 2 3 \ \ Comparative Example 4 5 6 7 Comparative preparation example of corrosion inhibitor 1 2 3 4 Performance Testing The coatings prepared in the examples and comparative examples were sprayed on the surface of the safety belt (including the metal part and the webbing part) according to the following steps: Spraying method: Use a spray gun with the pressure set at 0.4 MPa. Spray at a distance of 20 cm from the surface of the safety belt. First dry it at 25°C and 50% humidity for 3 hours, then place it in a drying oven at 70°C for 2.5 hours to form a coating. The coating thickness is controlled to be 100 μm.

[0041] The uncoated safety belts and the coated safety belts were subjected to the following performance tests, and the test results are recorded in Table 3.

[0042] Detection Methods 1. Corrosion current density test: The test is carried out according to GB / T 24196-2009 "Guide for constant potential and dynamic potential polarization measurements of electrochemical test methods for corrosion of metals and alloys".

[0043] 2. Salt spray corrosion resistance test: The test is carried out according to GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", and the test liquid is a 3.5% sodium chloride solution; The test cycles are 900h, 1000h, 1100h, 1200h, 1300h, 1400h, 1500h, 1600h, 1700h, 1800h, 1900h, 2000h, 2100h and 2200h. After the test, observe the appearance of the seat belts.

[0044] 3. Adhesion test: Test according to GB / T 5210-2006 and record the tensile force value when the coating is damaged.

[0045] Table 3 Performance test results Referring to the data in Table 3, it can be seen that compared with the uncoated safety belts, the corrosion current density of the safety belts coated with the coatings of Examples 1-3 is reduced by more than 80%, indicating that the coating can significantly improve the corrosion resistance of the metal substrate in seawater; after testing for 1400 hours, the coating is intact, without bubbles or peeling, indicating that the coating effectively improves the waterproof performance of the webbing.

[0046] The difference between Comparative Example 3 and Example 2 is that the same amount of sodium oleate is used instead of the corrosion inhibitor, and the coating can only be intact for 1100 hours, but the actual object feels greasy. This shows that the application uses ammonium salt and nanoclay with sodium oleate, which can not only improve the waterproof effect, but also not feel greasy.

[0047] The difference between Comparative Examples 4-5 and Example 2 is that the corrosion inhibitor used does not contain sodium salt or nanoclay, and the coating integrity time of the prepared coating can only reach 1000-1100h after testing, and the waterproofness is significantly reduced. At the same time, the amount of ammonium salt and nanoclay in the corrosion inhibitor of Comparative Examples 6-7 is changed, and the waterproof effect is also reduced. It shows that only when the corrosion inhibitor is compounded by the three at the same time and under a certain dosage ratio, the coating can have an excellent waterproof effect.

[0048] The possible reason is that the ammonium salt cation carries a positive charge and can be adsorbed between the negatively charged nanoclay layers, while the other end adsorbs the oleate ion which is negatively charged in water, thereby fixing the sodium oleate between the nanoclay layers, and then making the sodium oleate firmly adsorbed on the fiber surface, improving the detachment problem.

[0049] The difference from Example 2 is that in Example 1, reducing the amount of corrosion inhibitor resulted in the coating integrity time being reduced to 900 hours, while in Example 2, increasing the amount of corrosion inhibitor did not significantly improve the coating integrity time, and the adhesion decreased. Considering the cost, the amount of corrosion inhibitor should be within the range of Examples 1-3.

[0050] The difference from Example 2 is that the amounts of sodium oleate, ammonium salt and nanoclay in the corrosion inhibitors in Examples 4-5 are different, so that the safety belt can maintain the integrity of the coating for more than 1800-2100 hours, and the waterproofness of the coating is significantly improved.

[0051] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A surface coating for a safety belt that is resistant to seawater erosion, characterized in that: The components include the following weight fractions: Polyurethane resin 26-35 parts; 3-8 parts of filler; 8-16 parts of corrosion inhibitor; 3-9 parts of plasticizer; 30-55 parts of solvent; 5-10 parts of coupling agent; The raw materials for preparing the corrosion inhibitor include: ammonium salt, nano clay and sodium oleate.

2. The surface coating for protecting a safety belt from seawater erosion according to claim 1, characterized in that: The preparation method of the corrosion inhibitor comprises the following steps: adding ammonium salt and nano clay into water, mixing, then adding sodium oleate, mixing, ultrasonically dispersing, filtering to remove filtrate, and drying to obtain the corrosion inhibitor.

3. The surface coating for protecting a safety belt from seawater erosion according to claim 2, characterized in that: The weight ratio of the sodium oleate, the ammonium salt and the nano clay is 1:0.8-1.2:0.3-0.

5.

4. The surface coating for protecting a safety belt from seawater erosion according to claim 2, characterized in that: The amine salt has 12-18 carbon atoms.

5. The surface coating for protecting a safety belt from seawater erosion according to claim 4, characterized in that: The amine salt is one of lauryl ammonium sulfate, hexadecyl ammonium chloride and octadecyl quaternary ammonium salt.

6. The surface coating for a safety belt that is resistant to seawater erosion according to claim 1, characterized in that: The filler is graphene nanosheets.

7. The surface coating for protecting a safety belt from seawater erosion according to claim 1, characterized in that: The plasticizer is dioctyl phthalate.

8. The surface coating for protecting a safety belt from seawater erosion according to claim 1, characterized in that: The solvent is one of toluene and xylene.

9. A method for preparing the surface coating for a safety belt that resists seawater erosion according to any one of claims 1 to 8, characterized in that: The following steps are involved: The polyurethane resin, filler, corrosion inhibitor, plasticizer, solvent and coupling agent are mixed to obtain the product.

Citation Information

Cited By

  • Corrosion-resistant water-based paint and preparation process thereof

    CN120349696A